A Chemical Chaperone‐Based Drug Candidate is Effective in a Mouse Model of Amyotrophic Lateral Sclerosis (ALS). Issue 5 (13th March 2015) - Getter, Tamar; Zaks, Ilana; Barhum, Yael; Ben‐Zur, Tali; Böselt, Sebastian; Gregoire, Simpson; Viskind, Olga; Shani, Tom; Gottlieb, Hugo; Green, Omer; Shubely, Moran; Senderowitz, Hanoch; et al.
Abstract Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by the selective death of motor neurons and skeletal muscle atrophy. The majority of ALS cases are acquired spontaneously, with inherited disease accounting for only 10 % of all cases. Recent studies provide compelling evidence that aggregates of misfolded proteins underlie both types of ALS. Small molecules such as artificial chaperones can prevent or even reverse the aggregation of proteins associated with various human diseases. However, their very high active concentration (micromolar range) severely limits their utility as drugs. We synthesized several ester and amide derivatives of chemical chaperones. The lead compound 14, 3‐((5‐((4, 6‐dimethylpyridin‐2‐yl)methoxy)‐5‐oxopentanoyl)oxy)‐N, N‐dimethylpropan‐1‐amine oxide shows, in the micromolar concentration range, both neuronal and astrocyte protective effects in vitro; at daily doses of 10 mg kg−114 improved the neurological functions and delayed body weight loss in ALS mice. Members of this new chemical chaperone derivative class are strong candidates for the development of new drugs for ALS patients.